Student Experience Outcomes in Racially Integrated Schools: Looking Beyond Test Scores in Six Districts. Issue 3 (March 2022) - Schneider, Jack; Piazza, Peter; White, Rachel S.; Carey, Ashley
In this study, we examine eight social and emotional outcomes (e.g., student engagement, sense of belonging) analyzing differences for students who attend racially diverse schools. Drawing on survey responses from roughly 26, 000 students, we find that racially diverse schools are associated with more positive social and emotional outcomes for all students. Strikingly, we find that these outcomes are most uniformly positive among white students, whose families have long represented the strongest opposition to systematic racial desegregation. In light of these results, this study has implications for educators, advocates, researchers, and policy makers during a time of renewed attention to school integration.